EFFECTS OF WHEAT BRAN DIET AND MAIZE BRAN DIET ON THE RANDOM BLOOD GLUCOSE AND WEIGHT OF ALLOXAN INDUCED DIABETIC RATS - A. Hamid; M. Ilyas; S. Kalsoom; N. Bhatty (Journal of Animal and Plant Sciences, 2017)
The present study was conducted to evaluate the effect of wheat and maize brans feeds on the random blood glucose of the rats. These feeds were prepared using the  the Purified Diet AIN-93-G with some modifications. The experiment was laid out under completely randomized design. The rats (n=24) of almost uniform age and weight were divided into 4 groups each containing 6 rats. Group I comprised rats with normal blood glucose level reared on basal diet (AIN-93-G), Group II was Alloxan monohydrate (ALX monohydrate) induced diabetic rats reared on Purified Diet AIN-93G. Group III comprised Alloxan monohydrate induced diabetic rats fed a wheat bran diet and Group IV consisted of Alloxan monohydrate induced diabetic rats reared on a maize bran diet. The Random Blood Glucose (mg/dL) of these groups was monitored at the end of each week for a period of 6 weeks. Bran diets (maize and wheat) significantly lowered the Random Blood Glucose level in the experimental animals.  However,the group of rats fed on maize bran diet  had a significantly (p<0.05) more pronounced glucose lowering as compared to the group of rats fed on wheat bran diet. The results indicated that both wheat and maize bran exert anti-diabetic effects on the ALX monohydrate induced diabetes and therefore, can be a part of diet based therapy for the management of diabetes.
Keywords: Wheat Bran; Maize Bran; random blood glucose; Purified Diet (PD AIN-93G).